2021
DOI: 10.1108/jes-07-2020-0328
|View full text |Cite
|
Sign up to set email alerts
|

The impact of monetary policy on income inequality: evidence from Eurozone markets

Abstract: PurposeThis study examines the impact of monetary policy on income inequality in Eurozone countries for the period between 2005 and 2017.Design/methodology/approachThe authors use regression analysis, panel vector autoregression (PVAR) analysis and impulse response functions, in order to examine the impact of monetary policy on income inequality in Eurozone countries.FindingsThis study examines the impact of monetary policy on income inequality in Eurozone countries for the period between 2005 and 2017. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Specifically, monetary policy can The empirical findings imply that China's easy monetary policy further expanded the income disparity between urban and rural areas. This finding is similar to the studies of Taghizadeh-Hesary et al [59] and Liosi and Spyrou [79], which argue that easy monetary policy worsens income inequality levels. However, unlike previous studies, we find that the effect of monetary policy on the urban-rural income disparity in China has a time-varying feature.…”
Section: The Time-varying Effects Of Monetary Policy On Urban-rural I...supporting
confidence: 91%
“…Specifically, monetary policy can The empirical findings imply that China's easy monetary policy further expanded the income disparity between urban and rural areas. This finding is similar to the studies of Taghizadeh-Hesary et al [59] and Liosi and Spyrou [79], which argue that easy monetary policy worsens income inequality levels. However, unlike previous studies, we find that the effect of monetary policy on the urban-rural income disparity in China has a time-varying feature.…”
Section: The Time-varying Effects Of Monetary Policy On Urban-rural I...supporting
confidence: 91%
“…Both theoretical and empirical studies also witness that, in addition to the declining labour share, other factors driving inequality could be high inflation (Siami-Namini and Hudson 2019;Liosi and Spyrou 2022;Tomkiewicz 2018), poor governance (Bahamonde and Trasberg 2021), low financial development (Kim 2016) and some structural factors such as the share of the shadow economy (Yap et al 2018) or share of manufacturing employment compared to agriculture and service (Pariboni and Tridico 2019;Vo et al 2019). Conversely, effective government can and should reduce inequality in several ways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study conducted in Sri Lanka, Kim & Samarasekara (2022) found that public expenditure is ineffective for the policy objective; instead, it raises inequality. Liosi and Spyrou (2022) pointed out that, on average, monetary policy positively impacts income inequality. A more detailed analysis demonstrates that for Ireland, Germany and the Netherlands, monetary policy has no effect on income inequality or a weak impact (France).…”
Section: Introductionmentioning
confidence: 99%